“Kalibokong Theology” and Moeslim Abdurrahman’s Transformative Islamic Education - Zuly Qodir (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2017)
This paper discusses the idea of Transformative Islamic Education with Teologi Kalibokong as the illustration. Teologi Kalibokong is used by Moeslim Abdurrahman to describe the disadvantaged situations endured by marginal societies for being exploited by middlemen and capitalists. Nevertheless, those situations cover many aspects including social, economy, education, and politics. From the perspective of Islamic jurisprudence, marginal society becomes a group of people who are less religious. They are presumed as less religious believers. Related to this, Moeslim Abdurrahman introduces the significance of particular theology for the oppressed (al-mustad'afin), which is the building of Islamic theology as the spirit of Transformative Islamic Education that generates people who capable of breaking the impasse of social injustice with critical Islamic and non-judgmental approaches.